2017
DOI: 10.1007/s00005-017-0473-7
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-23 Receptor, IL-17A and IL-17F Gene Polymorphisms in Brazilian Patients with Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a progressive, autoimmune disease for which the previous studies have shown that some functional polymorphisms can influence its etiology. Knowing this, the aim of this study was to investigate the association of +2199 A/C IL-23R (rs10889677), -197 G/A IL-17A (rs2275913), and +7488 A/G IL-17F (rs763780) gene polymorphisms with RA susceptibility and clinical features in a Brazilian population. A total of 127 RA patients and 134 healthy controls were recruited for the analyses of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Again, most of published studies performed in Algerian [ 27 ], Polish [ 28 , 29 ], Brazilian [ 30 ] and Chinese [ 31 ] populations emphasized the lack of association between the IL-17A rs2275913 and RA risk. Nevertheless, two studies performed in Norwegian [ 32 ] and Brazilian [ 33 ] reported that the rs2275913 polymorphism increased risk of RA. In Norwegian patients, the IL-17A*G allele conferred a weak risk, OR = 1.17, 95% CI = 1.02–1.34 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, most of published studies performed in Algerian [ 27 ], Polish [ 28 , 29 ], Brazilian [ 30 ] and Chinese [ 31 ] populations emphasized the lack of association between the IL-17A rs2275913 and RA risk. Nevertheless, two studies performed in Norwegian [ 32 ] and Brazilian [ 33 ] reported that the rs2275913 polymorphism increased risk of RA. In Norwegian patients, the IL-17A*G allele conferred a weak risk, OR = 1.17, 95% CI = 1.02–1.34 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Norwegian patients, the IL-17A*G allele conferred a weak risk, OR = 1.17, 95% CI = 1.02–1.34 [ 32 ]. While the risk for RA was moderate for the IL-17*G/G genotype, OR = 3.18, 95% CI = 1.13–9.95 in the Brazilian study [ 33 ]. Accordingly, the meta-analysis of Lee et al [ 17 ] the IL-17A*A allele conferred a weak protective role for RA risk, OR = 0.866; 95% CI = 0.794–0.944.…”
Section: Discussionmentioning
confidence: 99%
“…Our group already reported that the AA genotype and A allele for IL17A were associated with susceptibility to chronic periodontitis in South Brazil, highlighting their involvement in a chronic inflammatory condition [ 18 ]. A weak association between rheumatoid arthritis and the promoter IL17A rs2275913 was found in the Norwegian population and more recently in the Brazilian population [ 7 , 32 ]. Specifically, with the risk of AS and its severity, a strong association was observed with the rs4819554 SNP in the promoter region of IL17RA in two Spanish cohorts of patients and controls, but not involving the IL17A and IL17F polymorphisms that we have studied here [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In PsA, treatment with anti‐IL‐23 antibodies have shown beneficial effects but not in RA so far. Another finding supporting this hypothesis, is the notion that polymorphisms in the IL‐23 receptor (IL‐23R) have been linked to susceptibility for psoriasis and PsA , but are still a matter of debate in RA (Table ) .…”
Section: Introductionmentioning
confidence: 97%